An explanatory model of potential changes in burnout diagnosis according to personality factors in oncology nurses - Fuente -Solana, Emilia I. de la; Castañas, Gustavo R.; Ramírez-Baena, Lucía; Gómez-Urquiza, José Luis; Ariza, Tania; Cañadas-De la Fuente, Guillermo A. (International Journal of Environmental Research and Public Health, 2019)
Burnout in a hospital oncology service takes place when there is a high level of interaction between nurses and patients. The aim of the present study is to identify models that will enable us to accurately classify a person at a given level within each of the three dimensions of burnout, according to the values presented for personality related explanatory variables, for a sample of 96 oncology nurses working in the regional health service of Andalusia (Spain). A quantitative, crosscutting, multicentre, descriptive study was designed, and for this purpose data on sociodemographic and personality variables and on the three dimensions of burnout were compiled. Three categorical-response logit ordinal models were used and the prognostic ratios for each level were obtained, with respect to every other level, according to possible changes in the explanatory variables considered. Certain personality factors are associated with one or more dimensions of burnout syndrome. Thus, nurses are more likely to develop high levels of burnout if they present high levels of neuroticism and low levels of friendliness and responsibility. Further research in this field is needed to confirm and extend these findings.
Keywords: burnout; nursing; oncology; personality; risk factors; Scopus; JCR